Materials and technologies in mechanical engineering : special topic volume with invited peer reviewed papers only - Chinakhov, Dmitry A. (Trans Tech Publications, 2018)
This special issue contains research papers on modern technologies for obtaining and processing materials, technologies for obtaining welded joints and additive technologies. The book is intended for a wide range of specialists engaged in the development and production of heavy-duty metal structures, as well as for students, undergraduates, graduate and postgraduate students of technical colleges and universities. Steel, Alloys, Intermetallic Compound, Composites, Welding, Ion-Plasma Treatment, Welded Joints Materials Science.